IMPROVING ORGANIZATIONAL ARCHIVAL MANAGEMENT THROUGH AN APPSHEET-BASED DIGITAL SYSTEM - Khalizah Alfi Fadhliyah; Roni Faslah; Rayi Dwipanilih (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to develop and evaluate the feasibility of an AppSheet-based archival media to support the management of customer inquiry document archives in the Marketing Department of PT XYZ. The research method employed was Research and Development (R&D) using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through validation by media experts and subject-matter experts, as well as a user acceptance test conducted by the company. The evaluation instruments used Likert scale and were analyzed using descriptive quantitative techniques. The results indicate that the AppSheet-based archival media achieved a feasibility score of 95% from media experts and 100% from subject-matter experts, both classified as “Very Suitable” The user acceptance test also yielded a 85,33% feasibility score, indicating that the application can be used without functional constraints. The developed archival media improves storage organization, accelerates archive retrieval processes, and supports more efficient archival reporting.